PENERAPAN AUGMENTED REALITY BERBASIS ANDROID SEBAGAI MEDIA PENAMPIL INFORMASI TAMBAHAN PADA BROSUR PENERIMAAN MAHASISWA BARU UNIVERSITAS PANCA MARGA - Januar Bagus Prasetyo; Nuzul Hikmah; Muhammad Fathuddin Noor (JURNAL TEKNIK INFORMATIKA, 2021)
Augmented Reality is a type of interactive technology that combines real objects and virtual objects at the same time and is displayed on the screen. Augmented Reality has been applied as a way of working based on image detection and it is commonly called a marker. By using the smartphone's camera and then detects the marker that has been printed. Augmented Reality is widely used in various purposes, the example is for advertising or promotion. In advertising, Augmented Reality can be used as a promotion or information that can make it more interesting. This research aims to apply AR technology to the campus promotion media on the University of Panca Marga's new student admission brochure. The stages taken in this research are literature study as well as observation, design, and implementation stages. The application of Augmented Reality was built using Unity 3D software, Android SDK, Vuforia SDK, and Sweet Home 3D. The results of the application of Augmented Reality technology can display 3D virtual objects, 2D, and video using the new student admission brochure used as a marker. The marker that is detected by the camera on the Android smartphone can display 3D UPM buildings, location plans, UPM profile videos, and faculty digital brochures. So users can see how the campus buildings are in real-time as well as some other information that has been provided. Based on the tests, all features can run well.